Research Note—Perceived Firm Attributes and Intrinsic Motivation in Sponsored Open Source Software Projects - Spaeth, Sebastian; von Krogh, Georg; He, Fang (Information Systems Research, 2015)
Voluntary contributions are crucial to the success of open source software (OSS) projects. Firms sponsoring OSS projects may face substantial challenges in soliciting such contributions, since volunteer participants are neither regulated by an employment contract nor offered financial incentives. Although prior work has shown the positive impact of motivation on the effort expended by volunteer participants, there is limited understanding of how specific firm attributes shape volunteers’ intrinsic motivation. We offer a theoretical model of how the perceived community-based credibility and openness of the sponsoring firm have a positive impact on the intrinsic motivation of volunteer participants. The model is explored using survey data on volunteer participants from two sponsored OSS projects. Results show that a sponsoring firm’s community-based credibility (OSS developers’ perception of its expertise and trustworthiness) and openness (its mutual knowledge exchange with the community) strengthen the volunteer participants’ social identification with the firm-sponsored community, which in turn reinforces their intrinsic motivation to participate. Moreover, the perceived community-based credibility of a sponsoring firm directly enhances volunteer participants’ intrinsic motivation, whereas perceived openness fails to affect motivation without the mediating mechanism of social identification. Implications for firms seeking voluntary contributions for their sponsored OSS projects are discussed.